An Overview of Extraction Methods of Bioactive Compounds from White Mulberry (Morus alba) Leaf - Witoyo, Jatmiko Eko; Utoro, Panggulu Ahmad Ramadhani; Alvianto, Dikianur; Naisali, Hyldegardis (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2024)
White mulberry (Morus alba) is a plant classified into the Morus genus and the Moraceae family, growing wild or cultivated in Indonesia. The mulberry fruit is the plant part that is more utilized than others. However, white mulberry leaves are abundant and contain bioactive and nutraceutical compounds, which benefit the medicine and food sectors, making them an exciting material to investigate further. The method used in this study was a literature review, in which data from earlier studies were collected from open-access database sources, especially Google Scholar, from 2006 to 2023. The results showed that the white mulberry leaf contains rich bioactive compounds such as alkaloids, anthraquinone, anthocyanin, flavonoids, glycosides, phenolic acids, saponins, steroids, tannic acids, and so on, which are revealed to have pharmacological activities, and also contain complete nutraceutical composition as promised as food ingredients. Extraction is the primary process for extracting bioactive compounds from white mulberry leaves. Maceration, microwave-assisted extraction (MAE), soxhlet, supercritical CO2 extraction, and ultrasonic-assisted extraction (UAE) were common methods to extract bioactive compounds and produce white mulberry leaf extracts with different characteristics. Therefore, this review highlights the effect of various extraction methods on the bioactive compounds of white mulberry leaf extracts, represented by total phenolic content (TPC) and total flavonoid content (TFC).Â